Non-invasive electrical and magnetic stimulation of the brain, spinal cord, roots and peripheral nerves: Basic principles and procedures for routine clinical and research application. An updated report from an I.F.C.N. Committee. Issue 6 (June 2015) - Rossini, P.M.; Burke, D.; Chen, R.; Cohen, L.G.; Daskalakis, Z.; Di Iorio, R.; Di Lazzaro, V.; Ferreri, F.; Fitzgerald, P.B.; George, M.S.; Hallett, M.; Lefaucheur, J.P.; et al.
Highlights: This review is an up-date document on basic aspects of non-invasive stimulation of brain, spinal cord and nerve roots. The main physiological, theoretical and methodological features of transcranial magnetic stimulation (TMS) are described. Instructions for practical use of non-invasive stimulation in clinical applications and research are provided. Abstract: These guidelines provide an up-date of previous IFCN report on "Non-invasive electrical and magnetic stimulation of the brain, spinal cord and roots: basic principles and procedures for routine clinical application" (Rossini et al., 1994 ). A new Committee, composed of international experts, some of whom were in the panel of the 1994 "Report", was selected to produce a current state-of-the-art review of non-invasive stimulation both for clinical application and research in neuroscience. Since 1994, the international scientific community has seen a rapid increase in non-invasive brain stimulation in studying cognition, brain–behavior relationship and pathophysiology of various neurologic and psychiatric disorders. New paradigms of stimulation and new techniques have been developed. Furthermore, a large number of studies and clinical trials have demonstrated potential therapeutic applications of non-invasive brain stimulation, especially for TMS. Recent guidelines can be found in the literature covering specific aspects of non-invasive brain stimulation, such as safety (Rossi et al., 2009 ), methodology (Groppa et al., 2012 ) and therapeutic applications (Lefaucheur et al., 2014 ). This up-dated review covers theoretical, physiological and practical aspects of non-invasive stimulation of brain, spinal cord, nerve roots and peripheral nerves in the light of more updated knowledge, and include some recent extensions and developments.